Every Picture Hides a Story: The Secret Ways Artists Make Their Work More Seductive - Gabrielle, Anna; Cane, William (Rowman & Littlefield Publishers, 2022)
Each year 11 million people trek to the Louvre to gawk at the Mona Lisa. Many visitors clutch guide books in hand describing the painting. For some, it’s the experience of a lifetime, one they’ll talk about with friends and family for decades. Yet some modern researchers say that the vast majority of people will never recognize the hidden messages in this painting. That’s because those hidden messages are subliminal. Buried below the threshold of conscious awareness, Da Vinci used techniques people never notice. Not only don’t people know what they’re seeing, they would be shocked to find out. A surprisingly large number of famous paintings fall into the same category. That is, they employ subliminal techniques to enhance the effectiveness of the work or to encode messages within portraits and landscapes. No book, however, has ever attempted to provide an overview of the technical sophistication and arcane methods that artists worldwide have used to conceal secret meaning in their work. Every Picture Hides a Story is the first book to expose the subliminal content in the world’s greatest paintings. Titillating, subversive, and building on the groundbreaking work of pioneers of art criticism, this book will enable readers to view art masterpieces with greater understanding. And their enjoyment of these works will be exponentially enhanced. This full-color book contains 86 images of the paintings and their details.